2008
DOI: 10.1902/jop.2008.070462
|View full text |Cite
|
Sign up to set email alerts
|

A Morphometric and Histopathologic Evaluation of the Effects of Propolis on Alveolar Bone Loss in Experimental Periodontitis in Rats

Abstract: The findings of this study provide morphologic and histologic evidence that propolis, when administered systemically, prevents alveolar bone loss in the rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
2
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 32 publications
5
56
2
8
Order By: Relevance
“…In many extant studies, the effects of antioxidants such as coenzyme Q 10 , propolis and N-acetylcysteine, vitamin C, cocoa, proanthosianidine, and statins have been evaluated in experimental periodontitis (30,(43)(44)(45)(46). However, no work has been done thus far on the antioxidant activity of melatonin upon heart tissue in the presence of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In many extant studies, the effects of antioxidants such as coenzyme Q 10 , propolis and N-acetylcysteine, vitamin C, cocoa, proanthosianidine, and statins have been evaluated in experimental periodontitis (30,(43)(44)(45)(46). However, no work has been done thus far on the antioxidant activity of melatonin upon heart tissue in the presence of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse effects are common at dosages .15 g/d in human and animal studies. 31,32 The most common adverse effects are allergic reactions and skin or mucous membrane irritations. 32 In our study we used propolis at a dose of 100 mg/kg and found no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for using this experimental period is based on previous investigations. 13,15,23 According to Lima et al, 23 placement of a ligature around the molar teeth of rats leads to the presence of inflammatory cells, including osteoclasts, beneath the ligature. These authors reported that the substantial alveolar bone loss originated on day 3 of periodontitis induction reached a maximum between days 7 and 11.…”
Section: Discussionmentioning
confidence: 99%
“…The ligatures were kept in position in order to allow biofilm accumulation for 11days. 15,16 The contralateral tooth was left unligated for use as a control.…”
Section: Experimental Periodontal Diseasementioning
confidence: 99%